Mengukur Implementasi Platform Media Sosial terhadap Strategi Digital Marketing UMKM - Deviana Nurul Sholekha; Yusi Yulianiza; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to explore the implementation of social media platforms in supporting digital marketing strategies for micro, small and medium businesses. Using a descriptive qualitative approach, data was collected through literature study, direct observation, and semi-structured interviews with 6 to 12 business actors who actively use social media. Thematic analysis techniques are used to identify patterns of utilization of platforms such as Instagram, Facebook, and TikTok, as well as the challenges faced. The research results show that social media provides a great opportunity for businesses to increase visibility, reach a wider audience, and strengthen relationships with customers. Instagram offers visual power, Facebook allows specific market segmentation, and TikTok provides high virality potential. However, business actors face obstacles such as limited technical knowledge, limited resources, and competition with big brands. This research concludes that a deep understanding of platform features, consistency in creating content, and adaptation to market trends are very important for the success of a digital marketing strategy. With the right strategy, social media can become the main pillar in supporting business growth and competitiveness in the digital era.